2017
DOI: 10.3390/v9080228
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Frames, the State of Research on the Alphavirus 6K and TF Proteins

Abstract: For 30 years it was thought the alphavirus 6K gene encoded a single 6 kDa protein. However, through a bioinformatics search 10 years ago, it was discovered that there is a frameshifting event and two proteins, 6K and transframe (TF), are translated from the 6K gene. Thus, many functions attributed to the 6K protein needed reevaluation to determine if they properly belong to 6K, TF, or both proteins. In this mini-review, we reevaluate the past research on 6K and put those results in context where there are two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 152 publications
(254 reference statements)
0
24
0
2
Order By: Relevance
“…Nucleocapsids containing one copy of the genome interact with the cytoplasmic tails of viral glycoproteins to promote the budding of new virus particles [ 62 ]. At only 55 amino acids in size, the SINV 6K protein belongs to the viroporin family of proteins and is palmitoylated, helping it to target membranes [ 63 , 64 , 65 , 66 , 67 ]. The 6K protein is also involved in the transport of viral glycoproteins through the vesicular system to the plasma membrane [ 68 , 69 ].…”
Section: Overview Of the Sindbis Virus Life Cyclementioning
confidence: 99%
“…Nucleocapsids containing one copy of the genome interact with the cytoplasmic tails of viral glycoproteins to promote the budding of new virus particles [ 62 ]. At only 55 amino acids in size, the SINV 6K protein belongs to the viroporin family of proteins and is palmitoylated, helping it to target membranes [ 63 , 64 , 65 , 66 , 67 ]. The 6K protein is also involved in the transport of viral glycoproteins through the vesicular system to the plasma membrane [ 68 , 69 ].…”
Section: Overview Of the Sindbis Virus Life Cyclementioning
confidence: 99%
“…TF then undergoes unique post-translational modifications respective to 6K and is integrated into the envelopes of mature virions (17). Although the biological function of TF is poorly understood (18), it has been hypothesized to function as an ion channel, similar to its 6K counterpart (19). A study with SINV mutants that disrupted production of TF resulted in reduced virus production in mammalian and insect cell lines that was independent of genome replication, particle infectivity, or envelope protein transport to the cellular membrane.…”
mentioning
confidence: 99%
“…The TF (~8.3 kDa) protein possess the same N terminus as 6 K (61 amino acids~6.6 kDa) but differs by having a longer basic C terminus (~15 residues) instead of a shorter, hydrophobic C terminus found on 6 K [58,87,88]. Unlike other structural proteins, the exact functions of both 6K and TF have not been clearly elucidated [133]. However, studies on other alphaviruses have suggested that these viral accessory proteins mediate membrane permeability and viral budding, and may also be involved in forming ion channels [87,134,135].…”
Section: K/tf Proteinmentioning
confidence: 99%